Thwaites Glacier time series of surface elevations at (107.09 W, 75.48 S) from January 2012 to November 2020 - Bevan, Suzanne; Luckman, Adrian; Benn, Douglas (NERC EDS UK Polar Data Centre, 2021)
A time series of surface elevation at a point on Thwaites Glacier, West Antarctica. The point is on grounded ice and is upstream of a sub-shelf cavity on the west flank of the fast-moving core of Thwaites Glacier. There are a total of 88 points. First column = yyyy-mm-dd, second column = elevation in metres. The work was funded by NERC projects NE/P011365/1 and NE/S006605/1. : The points were extracted from digital elevation models (DEMs) based on an interferometric analysis of TanDEM-X satellite system synthetic aperture radar (SAR) data. Phase-scaling of the interferograms utilised the supplied orbit data. The DEMs were geocoded first using the RAMP DEM (Liu et al., 2015) and then, iteratively, using the DEMs themselves. The DEMs were calibrated in the vertical using an ICESat-2 point at (107.49°W, 75.47°S) acquired on 2018-11-05. Heights are relative to the WGS84 ellipsoid. Processing is described fully in the reference paper. : Feature tracking was carried out using Gamma Remote Sensing software 20190603. : 9. Via comparison with ICESat-2 data and in consideration of orbit uncertainty, the original DEMs have an estimated vertical uncertainty of ±3 m.